2002
DOI: 10.1001/jama.288.10.1269
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Grief

Abstract: In the United States, more than 2 million children and adolescents (3.4%) younger than 18 years have experienced the death of a parent. When death can be anticipated, as with a terminal illness, and even when the death is sudden, as in the September 11, 2001, attacks on the World Trade Center and Pentagon, physicians and other health care professionals have an opportunity to ameliorate the impact of the loss. Developmental factors shape adolescents' reactions and responses to the death of a parent. Recent rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
28
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(30 citation statements)
references
References 34 publications
1
28
0
1
Order By: Relevance
“…We also observed that short-term mortality from external causes varied with the child's age at bereavement, with the youngest age group suffering most, which indicates lack of intense care immediately after bereavement for very young children. The above observations highlight the fact that children's coping mechanisms and their understanding of death are related to their age-dependent developmental capacity [41],[49]. Yet, the overall risk of death remained high for more than 20 years independently of age at bereavement.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…We also observed that short-term mortality from external causes varied with the child's age at bereavement, with the youngest age group suffering most, which indicates lack of intense care immediately after bereavement for very young children. The above observations highlight the fact that children's coping mechanisms and their understanding of death are related to their age-dependent developmental capacity [41],[49]. Yet, the overall risk of death remained high for more than 20 years independently of age at bereavement.…”
Section: Discussionmentioning
confidence: 83%
“…In addition, social-behavioral consequences of parental death, such as the loss of a care giver, misbehaviors, and functioning impairment [20],[41][45] can increase the risk of death from injuries or other external causes. For example, parental suicide was associated with more transport accident deaths in our population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A possible explanation could be that the nature of the sample and losses differed between both studies. Children’s grief reactions are strongly shaped by their developmental capacities and may therefore be expressed differently than adult’s reactions (Christ, Siegel, & Christ, 2002; Miller, 2009). Furthermore, it is known that the cause of death may influence bereavement outcome (Djelantik et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Shame, isolation, secrecy, survivor guilt, economic deprivation, and cultural factors often stand as barriers to critically needed mental health services leaving youngsters more vulnerable to negative psychiatric sequelae. Ideally, mental health professionals can help support adaptive coping strategies and prepare the family to facilitate an adolescent's mastery of adaptive tasks posed by the terminal phase of the parent's illness, the death, and its aftermath (Christ et al 2002). At a minimum, bereavement counseling should be provided to facilitate constructive mourning followed by monitoring of the child's mental health over time.…”
Section: Discussionmentioning
confidence: 99%